2019
DOI: 10.1155/2019/2156475
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Natural Frequencies of Retaining Walls Using the Transfer Matrix Method

Abstract: The dynamic response magnitudes of retaining walls under seismic loadings, such as earthquakes, are influenced by their natural frequencies. Resonances can occur when the natural frequency of a wall is close to the loading frequency, which could result in serious damage or collapse. Although field percussion tests are usually used to study the health state of retaining walls, they are complicated and time consuming. A natural frequency equation for retaining walls with tapered wall facings is established in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Vibrations of retaining walls caused by dynamic (seismic) loading were investigated analytically using linear approximation 9 . Experimental and numerical results for concrete retaining walls under low-frequency dynamic loading were reported in 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Vibrations of retaining walls caused by dynamic (seismic) loading were investigated analytically using linear approximation 9 . Experimental and numerical results for concrete retaining walls under low-frequency dynamic loading were reported in 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Xu and Jiang (2019) used the transfer matrix method for the free vibration analysis of retaining wall [27]. Kang et al (2019) Based on the transfer matrix method, they suggested modeling for periodic graphene structures [28].…”
Section: Introductionmentioning
confidence: 99%
“…Bozdoğan&Khosravi Maleki/Kırklareli University Journal of Engineering and Science 5-1(2019)[15][16][17][18][19][20][21][22][23][24][25][26][27][28] …”
mentioning
confidence: 99%